The Research on Han Zhen and Zhou Liya’s Dance Drama Communication Strategies in the Context of New Media—The Case of Bilibili Account "Han Zhen &Zhou Liya Studio " (Journal of Global Arts Studies, 2024)
Background: Han Zhen and Zhou Liya are iconic figures in the field of Chinese dance drama in recent years. They have garnered widespread attention through new media platforms, achieving a remarkable balance between artistic value and market appeal. Objective: This study aims to conduct an in-depth analysis of Han Zhen and Zhou Liya’s dance drama communication strategies in the context of new media. Methods: The research adopts a mixed-methods approach, combining qualitative and quantitative analysis. Taking Han Zhen and Zhou Liya’s official Bilibili account, “Han Zhen & Zhou Liya Studio,” as a case study, a total of 60 video posts uploaded as of November 29, 2024, were selected as research data. Content analysis was employed to examine video content types and communication metrics. Results: The study reveals that Han Zhen and Zhou Liya emphasize a communication strategy that combines a relaxed and natural style with the artistic qualities of dance drama. This differentiated strategy effectively attracts a diverse and multidimensional audience for dance drama. Conclusion: Their communication practices provide concrete references for dance drama creators seeking to communicate effectively on new media platforms, while also offering deeper insights into audience needs and communication characteristics within the new media environment.
Keywords: Han Zhen; Zhou Liya; Dance Drama Communication; New Media